Exchange Rates and Firm Survival: an Examination With Turkish Firm-Level Data - Toraganlı, Nazlı; Yazgan, Mustafa Ege (Elsevier, 2016)
Micro-level empirical research has begun to obtain important results on the effects of currency variations on firms’ survival. The literature has, however, lacked a detailed analysis of the effects of exchange rates on firms’ survival behavior in emerging markets due to a scarcity of firm-level information. Using a firm-level dataset, we investigate the impact of currency appreciation on the survival behavior of Turkish firms in the manufacturing industries for 2002–2009. Our results suggest that real exchange rate appreciation decreases the probability of survival in the manufacturing industries. We also find that high-productivity firms have a higher probability of survival than low- productivity firms following an appreciation of the exchange rate. Our findings indicate that the negative effect of a 1% real appreciation of the domestic currency on the survival probability of a given firm ranges from 4.5 to 9%, providing evidence for the vulnerability of developing countries to exchange rate movements. This evidence indicates that, especially for emerging market economies, economic events and policies leading to an appreciation in the domestic currency should be managed cautiously.
Keywords: Emerging markets; Export; Firm-level; Survival; Exchange rate